Respuesta :
M = Tim's dollar amount
R = Rebecca's dollar amount
MR = Tim and Rebecca's dollars together
R = (M x 1/10) - 6
MR = M + ((M x 1/10) - 6)
MR = 70 + ((70 x 1/10) - 6)
MR = 70 + (7 - 6)
MR = 70 + 1
MR = 71
R = Rebecca's dollar amount
MR = Tim and Rebecca's dollars together
R = (M x 1/10) - 6
MR = M + ((M x 1/10) - 6)
MR = 70 + ((70 x 1/10) - 6)
MR = 70 + (7 - 6)
MR = 70 + 1
MR = 71
Answer:
Total amount both have together = $71
Step-by-step explanation:
Tim has the dollars = M
Rebecca is having = [tex]\frac{M}{10}-6[/tex] dollars
Total amount of money Tim and Rebecca are having = M + M/10 - 6
= (11M/10) - 6 dollars
Therefore the expression representing total amount of money = [(11x/10) - 6]
If Tim is having $70 then total amount both have together = [(11×70/10) - 6]
= (77 - 6) = $71
Therefore the expression for total amount is = [(11M/10)-6] dollars and
Total amount both are having together = $71